Translation model for cross-platform communication in SOA applications - Ibrahim, N.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Service-oriented architecture (SOA) can be described as a software paradigm to develop systems comprising of a collection of services of which the services communicate with each other to reach a specified goal. The communication does not only engage simple data passing but also involve the connection of two or more services coordinating the prescribed activities. In the case when services are distributed across multiple platforms, cross-platform communication is required in the coordination process. In the current implementation of SOA, several specifications and standards of web services are employed. However, the communication of SOA applications distributed across multiple platforms cannot be guaranteed due to differences in the specifications and web services standard supported by the different platforms. Translation Model is proposed to ensure the translation of communicated messages among different Web services hosted in different platforms. The aim is to provide a flexible translation process to support the cross-platform communication. As a proof of concept, the research work is implemented on a case study involving the real world SOA application on agent-based trading system. Â© 2016 IEEE.